2018
DOI: 10.1002/gj.3291
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon record of rivers' sediments in the North Qilian Orogenic Belt: Implications of the tectonic evolution of the northeastern Tibetan Plateau

Abstract: The North Qilian Orogenic Belt (NQOB) is an important element of the northern edge of the Tibetan Plateau, and several rivers run along it. Zircon U–Pb dating, trace elements, and Hf isotopic data derived from the sediments carried by the rivers have been used to deduce the crustal evolution of the NQOB. U–Pb ages obtained from detrital zircons found in the sediments of the Zamu, Zhuanglan, and Beida rivers can be divided into five major age groups, that is, 2,600–1,500, 1,500–1,100, 1,100–650, 550–400, and 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…The formation of granitoids and intermediate rocks in the Longshoushan area is closely related to the collision of the Alxa and Qilian‐Qaidam blocks, caused by the continuous reduction of the North Qilian Ocean in the Early Palaeozoic (Yang et al, 2018; Fu et al, 2019; Kang et al, 2019). Regarding the time limits for each stage of the collision, Song, Niu, Zhang, and Zhang (2009), Song et al (2013) suggested that the Qilian Ocean had completely closed ca.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of granitoids and intermediate rocks in the Longshoushan area is closely related to the collision of the Alxa and Qilian‐Qaidam blocks, caused by the continuous reduction of the North Qilian Ocean in the Early Palaeozoic (Yang et al, 2018; Fu et al, 2019; Kang et al, 2019). Regarding the time limits for each stage of the collision, Song, Niu, Zhang, and Zhang (2009), Song et al (2013) suggested that the Qilian Ocean had completely closed ca.…”
Section: Discussionmentioning
confidence: 99%
“…Detrital zircon grains from rivers in the western parts of the North Qilian Shan (location 1 on Figure 1B) yielded five major U-Pb peak ages at 273 Ma, 462 Ma, 756 Ma, 1835 Ma and 2440 Ma [92] (Figure 5a). Detrital zircons found in the river sediments from the central parts of the North Qilian Shan (location 2 on Figure 1B) can again be divided into five major U-Pb peak ages at 267 Ma, 443 Ma, 973 Ma, 1776 Ma and 2481 Ma [93] (Figure 5b). Detrital zircons from the Hei River (locations 3 on Figure 1B) still show five major U-Pb peak ages at 270 Ma, 450 Ma, 950 Ma, 1850 Ma and 2450 Ma, lacking the 756 Ma peak observed in the western North Qilian Shan River [91] (Figure 5c).…”
Section: Hei Rivermentioning
confidence: 94%
“…However, it seems that the Hei River does not reach the 756 Ma source observed in the western North Qilian Shan River. [92]), Central North Qilian Shan ((b), [93]), whole Hei River ((c), [90]) with those from the North Qilian Shan ((d), [6,35,36,90]).…”
Section: Hei Rivermentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, in provenance studies, detrital zircon grain ages are compared with ages of probable source terranes, which delivered sediments to the depositional basin (Margalef et al, 2016;Shi et al, 2020;Tong et al, 2019;Wang, Wu, et al, 2018). On the other hand, numerous studies have proved that U-Pb dating of detrital zircon grains is a useful tool to reconstruct the tectonic evolution of a sedimentary basin, as well as to infer sediment pathway (Chaudhuri, Banerjee, & Le Pera, 2018;Gärtner et al, 2016;Kang et al, 2019;Pulsipher & Dehler, 2019;Saha, Burley, & Banerjee, 2018;Zhao et al, 2020).…”
mentioning
confidence: 99%